2012
DOI: 10.1016/j.polymer.2012.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Influence of shear-induced crystallization on the electrical conductivity of high density polyethylene carbon nanotube nanocomposites

Abstract: Abstract:The relation between shear mixing time in the melt, polymer crystal size, and electrical conductivity is studied for high density polyethylene -carbon nanotubes nanocomposites with 2 the help of in-situ rheo-dielectric and rheo-small angle synchrotron X-ray scattering (SAXS) techniques. Results show that the memory of crystal structure obtained after melt-mixing is not easily removed by re-melting and annealing. The conductivity of composites shear-mixed for 20 min. cannot reach that of 10 min. sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…These results agree with others reported in the literature [50]. For instance Tao et al [51] also reported a decrease in conductivity with temperature for a composite of MWCNTs and polyethylene at higher temperatures (T > T m ) and was related to the phenomena of crystallization of polyethylene which would disconnect the conductive paths [51]. Other authors [40,52] also observed a continuous increase of conductivity with temperature below T m (positive temperature coefficient effect of the resistivity).…”
Section: Pani Systemsupporting
confidence: 89%
“…These results agree with others reported in the literature [50]. For instance Tao et al [51] also reported a decrease in conductivity with temperature for a composite of MWCNTs and polyethylene at higher temperatures (T > T m ) and was related to the phenomena of crystallization of polyethylene which would disconnect the conductive paths [51]. Other authors [40,52] also observed a continuous increase of conductivity with temperature below T m (positive temperature coefficient effect of the resistivity).…”
Section: Pani Systemsupporting
confidence: 89%
“…It can be observed in Figure 7 that the nanocomposite containing 2 wt% MWCNTs under RC exhibits a slightly higher maximum current of 20.77 nA and more conductive regions uniformly distributed in the matrix compared to that under SC, indicating more conductive networks formed. This may be due to the lower crystallinity and smaller crystallites at RC facilitating the formation of conductive pathways [21] [40]. The information on the crystallinity and crystallite sizes of HDPE/MWCNT nanocomposites was presented via the XRD and DSC results in the previous section (Table 2).…”
Section: The Scaling Law Of Classical Percolation Theory (Equation 4)mentioning
confidence: 99%
“…In the past few years, the dispersion, structure and properties of melt mixed HDPE/CNT nanocomposites have been extensively discussed in previous literature [18] [19] [20] [21]. Morcom et al [18] investigated the dispersion and reinforcing effect of multi-walled carbon nanotubes (MWCNTs) on the properties of a melt mixed HDPE/MWCNT composite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporating inorganic nanoparticles into organic polymers will improve the mechanical, thermal, optical and barrier properties. Commonly used inorganic additives include clay [1,2], SiO 2 [3][4][5], carbon nanotubes [6,7], and carbon nanofibers [8], among others. Polyaniline (PANI) is a potential material for commercial applications owing to its facile synthesis, relatively low cost, environmental stability, good processability, and unique optical, electrical and electrochemical properties [9,10].…”
Section: Introductionmentioning
confidence: 99%